Penerapan Teorema Titik Tetap Banach pada Sistem Persamaan Linear dalam Model Input-Output Leontief - Syamsuddin Mas'ud (PT. Lontara Digitech Indonesia, 2026)
This study applies the Banach fixed point theorem to the 2-sector Leontief input-output model using Picard iteration. The results show that the iteration converges to the exact solution (95,65) after 15 iterations with an error of less than 0,003 and an error ratio stabilizing around 0,5. This convergence rate is faster than the theoretical upper bound of 0,6, indicating that the method works efficiently. These findings complement previous theoretical studies with a complete numerical demonstration.